Development of digital comic learning media based on mobile learning on sterilization and explant planting materials in plant tissue culture courses - Tanjung, Aura Albizia; Harahap, Fauziyah; Khalisyah, Zhafira; Anwar, Syakila; Nazwari, Aura; Pasaribu, Fadilah; Sitompul, Naila Zahwa (Assimilation: Indonesian Journal of Biology Education, 2025)
This research aims to develop a digital comic by determining the feasibility and the effectiveness of using material in the plant tissue culture to help students understand the material presented in the course at the Department of Biology, Universitas Negeri Medan. Data collection techniques include observation, giving questionnaires, and giving instruments to instructional experts, material experts, and media experts. The research method used is Research and Development (RD), which uses the ADDIE development model. This development research resulted in the creation of a digital comic learning media based on mobile learning focused on sterilization and planting materials, developed using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model.  Feasibility test results indicated high approval ratings: 93.75% from instructional experts in the “highly feasible”, 84.5% from material experts in the “highly feasible”, and 95.4% from media experts in the “highly feasible”. Lecturer responses were also favorable, with scores of 79.9. Student responses were also highly favorable, with scores of 91 from an individual group, 90.2 from a small group, and 94.2 from a limited group. Based on the data analysis, digital comic learning media based on mobile learning is effective enough for use in plant tissue culture courses.